A dual drug-based hyperbranched polymer with methotrexate and chlorambucil moieties for synergistic cancer chemotherapy. Issue 36 (21st August 2020) - Liu, Chengfei; Li, Huixin; Li, Pengxiang; Liu, Caiping; Bai, Yang; Pang, Jun; Wang, Jingxia; Tian, Wei
Abstract : Dual drug-based hyperbranched polymer micelles simultaneously containing methotrexate and chlorambucil were constructed for synergistic cancer chemotherapy. Abstract : Drug-based hyperbranched polymers have attracted broad interest from scientists due to their attractive and distinctive characteristics in cancer chemotherapy. However, the only use of the single-drug treatment modality could lead to low or unsatisfactory anticancer activity because of the limited treatment strategy and multidrug resistance of tumour cells. In this work, a novel dual drug-based hyperbranched polymer (DHBP ) simultaneously containing methotrexate (MTX) and chlorambucil (Cb) was proposed to realize synergistic cancer chemotherapy. After modification with PEG, the obtained DHBP- g -PEG self-assembled into hyperbranched polymer micelles (HBPM s) in aqueous solution with a high drug loading capacity and stable drug transport. Notably, HBPM s with excellent controlled drug release in tumour cells exhibited an obviously superior synergistic effect and possessed significant therapeutic efficiency and in vitro anticancer activity, as compared to either the individual drug or mixture drug treatment group. All these results demonstrate that the unique advantage of HBPM s may have significant potential for application in the field of synergistic cancer chemotherapy.